2018
DOI: 10.1002/adma.201806164
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromism from Ultrathin Colloidal Sb2Se3 Nanowires Undergoing Reversible Growth and Dissolution in an Amine–Thiol Mixture

Abstract: between molecular isomers, a phase transition between inorganic solids, or a change in the crystalline phases of liquid crystals. [8] To date, many thermochromic materials have been reported and commercialized, such as leuco dyes, [9] thermotropic liquid crystals, [10][11][12] titanium and vanadium oxides, [13][14][15] and peptide-based polydiacetylene. [16][17][18] Among these examples, the liquid-based leuco dyes and liquid crystals are unique as they can easily be made to fill various shaped voids, can be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…10 Indeed, the alkahest is known to dissolve a wide range of bulk metal oxides, including, but not limited to, Ag 2 O, As 2 O 3 , Bi 2 O 3 , CdO, Cu 2 O, CuO, In 2 O 3 , GeO 2 , MnO, PbO, Sb 2 O 3 , SeO 2 , SnO, and ZnO. 5,[11][12][13][14][15][16] Through a mild dissolve and recover approach, the alkahest solvent system returns phase-pure binary metal chalcogenide thin lms from dissolved oxide precursors; for example, semiconductor inks for metal sulde thin lms can be derived from dissolved metal oxides, where the sulfur source is the thiol component of the alkahest. Moreover, phase-pure, complex multinary semiconductors can also be solution processed by simply dissolving multiple bulk precursors in the proper stoichiometric ratios with the alkahest solvent system.…”
Section: Introductionmentioning
confidence: 99%
“…10 Indeed, the alkahest is known to dissolve a wide range of bulk metal oxides, including, but not limited to, Ag 2 O, As 2 O 3 , Bi 2 O 3 , CdO, Cu 2 O, CuO, In 2 O 3 , GeO 2 , MnO, PbO, Sb 2 O 3 , SeO 2 , SnO, and ZnO. 5,[11][12][13][14][15][16] Through a mild dissolve and recover approach, the alkahest solvent system returns phase-pure binary metal chalcogenide thin lms from dissolved oxide precursors; for example, semiconductor inks for metal sulde thin lms can be derived from dissolved metal oxides, where the sulfur source is the thiol component of the alkahest. Moreover, phase-pure, complex multinary semiconductors can also be solution processed by simply dissolving multiple bulk precursors in the proper stoichiometric ratios with the alkahest solvent system.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to , has recently received great attention to be utilized in applications of batteries 51 , 52 , photoelectrical 53 , 54 , thermoelectric devices 55 and photovoltaic light absorber 56 , due to its prodigious properties such as an optimal bandgap (1-1.3 eV) 57 , 58 , hole mobility up to 42 59 , desirable environmental characteristic 60 , 61 , physiochemical stability 41 , low-cost 62 , and elevated thermoelectric power 24 , as well as interesting optoelectronic features with absorption coefficient larger than 105 (at short wavelength) 27 , 63 . Also, a good efficiency in the power conversion up to 9.2 as very recently reported by Li et al 64 On the other hand, is receiving growing research attention within the scientific community because of its gorgeous properties such as low crystallization temperature 65 , and topological insulators 66 .…”
Section: Introductionmentioning
confidence: 99%
“…When temperature changes were recorded using an infrared thermal (IRT) camera (Figure h), we found that BPM quickly converted the absorbed light into heat, with the solution mean temperature reaching 52.7 °C within 7 min under NIR irradiation (Figure S9b). Such high temperatures cause irreversible protein denaturation and cell membrane destruction, resulting in effective and rapid hyperthermic sterilization . Conversely, no significant temperature changes were observed in the PBS group with the same NIR irradiation.…”
Section: Results and Discussionmentioning
confidence: 97%
“…Such high temperatures cause irreversible protein denaturation and cell membrane destruction, resulting in effective and rapid hyperthermic sterilization. 43 Conversely, no significant temperature changes were observed in the PBS group with the same NIR irradiation. Here, we found that the solvent had an impact on photothermal performance (Figure S9a), with the heating rate of 2DM being lower in PBS than in deionized (DI) water.…”
Section: ■ Introductionmentioning
confidence: 90%